THE DEVELOPMENT OF LOBSTER PUERULUS (PANULIRUS ORNATUS AND P. HOMARUS) IN CAPTIVITY ENVIRONMENT - Saputra, Ishaaq; Priyambodo, Bayu (Indonesian Aquaculture Journal, 2023)
The present study was conducted to investigate the development of Panulirus ornatus and P. homarus puerulus larvae into juveniles in a captive environment. Pueruli were collected from the local fishermen and transported by air to the research facilities. Puerulus of each species were stocked into 3 floating plastic compartments (5 cm × 12 cm × 17 cm) with sufficient holes, aeration, and a filtration system until reached their first moulting. Results indicated that both puerulus species were completely moulted after 6 days of stocking with the survival rate of 100% and 93.3%. Moulting began on Day 5 for P. ornatus and Day 4 for P. homarus pueruli. The weight of P. ornatus increased significantly after the metamorphosis (P<0.05). The initial and final weights of P. ornatus were significantly greater than P. homarus (P<0.05). In addition, the total and carapace lengths of both species were significantly increased (P<0.05). Morphological observations indicated that there was a significant distinguishing feature such as the antenae form and body pattern colour of both species. In conclusion, proper handling of the pueruli according to each species is required to preserve the quality in order to achieve greater success in metamorphosis into juveniles.